Quaternized Chitosan-Capped Mesoporous Silica Nanoparticles as Nanocarriers for Controlled Pesticide Release - Lidong Cao; Huirong Zhang; Chong Cao; Jiakun Zhang; Fengmin Li; Qiliang Huang (Nanomaterials, 2016)
Nanotechnology-based pesticide formulations would ensure effective utilization of agricultural inputs. In the present work, mesoporous silica nanoparticles (MSNs) with particle diameters of ~110 nm and pore sizes of ~3.7 nm were synthesized via a liquid crystal templating mechanism. A water-soluble chitosan (CS) derivative (N-(2-hydroxyl)propyl-3-trimethyl ammonium CS chloride, HTCC) was successfully capped on the surface of pyraclostrobin-loaded MSNs. The physicochemical and structural analyses showed that the electrostatic interactions and hydrogen bonding were the major forces responsible for the formation of HTCC-capped MSNs. HTCC coating greatly improved the loading efficiency (LC) (to 40.3%) compared to using bare MSNs as a single encapsulant (26.7%). The microstructure of the nanoparticles was revealed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The pyraclostrobin-loaded nanoparticles showed an initial burst and subsequent sustained release behavior. HTCC-capped MSNs released faster than bare MSNs in the initial stage. Pyraclostrobin-loaded HTCC-capped MSNs with half doses of pyraclostrobin technical demonstrated almost the same fungicidal activity against Phomopsis asparagi (Sacc.), which obviously reduced the applied pesticide and enhanced the utilization efficiency. Therefore, HTCC-decorated MSNs demonstrated great potential as nanocarriers in agrochemical applications.